Impact of variable exhaust valve timing on diesel engine characteristics fueled with waste cooking oil biofuel blends: A numerical analysis - Patel S.; Torgal S.; Purohit T.; Kumar R.; Singh D.V.; Kanchan S.; Soudagar M.E.M.; Ahamad T.; Kalam M.A.; Patel M. (SAGE Publications Ltd, 2024)
The quantity of the conventional sources of energy such as petroleum, coal, and the deposits of hydrocarbon are limited in nature. The rapid growth is observed in the industrial and transportation section due to increase in population that has compelled the mankind to look for an alternative to conventional fuels. Biodiesel can be a potential substitute due to its ease of availability, accessibility, lower cost, and nontoxic characteristics. In this study, waste cooking oil (WCO) as the feedstock for biodiesel due to its abundance and low prices is chosen. It has been observed that the high prices of cooking oil have compelled people to reuse it multiple times, which can have negative health consequences such as inflammation, cholesterol issues, diabetes, and cancer. However, if people can obtain WCO at a reasonable cost, they will refrain from reusing it repeatedly. This article presents a numerical method that investigates the effects of variable exhaust valve timing on the performance, emissions, and combustion parameters of WCO and its different blends in a conventional mechanical fuel injection system diesel. The study was conducted using a single-cylinder, water-cooled, in-line diesel engine running at a constant speed. As, it is not possible to determine the values of engine performance, emissions, and combustion parameters for different valve timings experimentally, a numerical method has been adopted. The valve timing range was taken as 4666 before bottom dead center (BDC) for exhaust valve opening and 620 after top dead center (TDC) for exhaust valve closing and the inlet valve opening and closing are constant at 16 b TDC and 33 a BDC, respectively. IMechE 2023.